PENGAMATAN ANGKA PEROKSIDA DAN ANGKA ASAM DALAM MEDE GORENG SELAMA PENYIMPANAN - Siti Isnijah S.P.; Jamilah Jamilah; Hilyati Hilyati (Jurnal Kimia Terapan Indonesia, 1993)
Cashew nut is a kind of seed consumed usually as fried snack food. Deterioration due to oxidative rancidity as well as hydrolisis of fat may decreas the quality of the fried cashew nut. In this paper the peroxide value and acid value of fried cashew nut during storage is discussed. Peroxide value and acid values were determined by titrimetrlc method while the change of unsaturated fatty acids were analyzed by using gas chromatography after transformation into methyl esters. Such analysis subjected to fried cashew nut using several kinds of frying oil, namely: palm oil, coconut oil and mixed palm and soybean oils. Sample was analyzed immediately after frying process (t=O), after 2 weeks (t=2) , 4 weeks (t=4) and 6 weeks (t=6) in storage. The peroxide values of the raw cashew nut and fried one using palm oil were high at t=6, 98.91 and 91.21 meqlkg oil respectively while the values of fried cashew nut using coconut oil for mixed palm oil with soybean oil have decreased, namely 28.85 or 8.62 meqlkg oil respectively. The acid values of raw cashew nut, the fried ones using coconut oil and mixed palm oil wilh soybean oil increased up to t=4, namely: 1.96%, 1.62% and 1.45% respectively. However, acid value of fried cashew nut using palm oil decreased, this was 1.25%.